POPULAR ISLAMIC CULTURE ON SOCIAL MEDIA: THE REPRESENTATION OF DA'WAH AMONG GENERATION Z MUSLIMS - Khaled Ibrahim Al-Rashidi; Edy Kisyanto; M Arifin (Universitas Islam Depok, 2026)
The rapid growth of social media has significantly transformed Islamic religious communication, especially among Generation Z, the first fully digital-native generation. This study explores how popular Islamic culture is represented and disseminated through social media platforms, focusing on the forms of da'wah consumed and produced by Muslim youth. It examines the communication strategies, digital formats, and cultural dynamics that shape contemporary Islamic messages in online spaces. Using a systematic literature review approach, the study analyzes 20 peer-reviewed empirical articles published between 2021 and 2025 from contexts such as Indonesia, Malaysia, Qatar, and the wider global Muslim community. The analysis is grounded in theories of digital Islam, da'wah communication, popular culture, and sociology of religion. The findings identify four major trends: dawahtainment, which combines Islamic messages with entertainment; the democratization of religious authority through social media influencers; the use of viral aesthetics, humor, and digital trends in conveying Islamic values; and the emergence of moderate Islamic narratives as responses to online radicalism. Generation Z actively negotiates between religious authenticity and entertainment, using digital Islamic content for identity formation, spiritual growth, and social belonging. The study concludes that popular Islamic culture on social media represents an adaptive and dynamic form of da'wah suited to the digital environment of Generation Z.